Etične dileme in vprašanja v fizioterapiji - Puh, Urška (Rehabilitacija (Ljubljana), 2017)
The evolution of professional ethics in physiotherapy, which is adapting to the changes in the profession and the social environment, is described. Increased clinical autonomy has increased the responsibility of physiotherapists, which entails the obligation to identify and confront ethical dilemmas and questions in physiotherapy practice. Ethical decisions must frequently be made by physiotherapists. The ethical dilemmas and questions that are frequently faced by physiotherapists working in the public health care system, the specifics of the private practise physiotherapy, and research ethics are summarised and described chronologically. The ethical principles of the Word Confederation for Physical Therapy may help to solve some ethical dilemmas. Despite the likely influence of the characteristics of the health care systems in the countries where the ethical dilemmas in physiotherapy have been studied, we believe that the findings from our literature review are at least partially applicable to Slovenia, where this topic has not been researched yet.
Keywords: code of ethics; ethical issues; Ethics; etični kodeks; etika; fizikalna terapija; fizioterapija; physiotherapy; Rehabilitation